Consumed yet quickened by the glance of God: John Henry Newman's Theology of Purgatory - McLaughlin, S (2014)
This thesis outlines the development of the doctrine of Purgatory in the theology of the nineteenth century theologian John Henry Newman (1801-1890). I trace the beginning of this development from 1816-1828 by identifying key theological themes from Newman’s early Evangelical writings on holiness, purification and conversion. After rejecting the Evangelicalism of his youth, Newman moved progressively towards High-Church Anglicanism from 1828 onward, and adopted the Anglican teaching of the 'intermediate state'. From 1830 he began to preach on this teaching by presenting it as an alternative to the 'depressing prospect' to the 'Romish' doctrine of Purgatory. However from 1837-1845 his views on Purgatory shifted considerably after studying the Tridentine decrees. In 1841 he claimed in Tract XC of Tracts for the Times that significant changes in the formulation of Article XXII of the XXXIX Articles meant that the Church of England did not reject the doctrine of Purgatory in its primitive form, but rather only the 'Romish' extremes of mediaeval theology which had corrupted her teaching. His claim that there was no disparity between what Trent taught on Purgatory and what the Church of England held in Article XXII caused widespread controversy among his contemporaries. In his early Roman Catholic years, from 1845-1853, he initially adopted the commonly held punitive model of Purgatory, but leaned increasingly towards an ameliorative understanding of the doctrine. By 1865 Newman had adumbrated a theology of Purgatory in The Dream of Gerontius, in which he showed how rather than being purged by material fire, the soul was purified by a singular and instantaneous experience of the holiness of God. I demonstrate how his theology of Purgatory in the Dream represents a significant contribution to a renewed understanding of the doctrine in Roman Catholic theology.